Isolation of Fungal Endophytes from Grasses by Laser Micro Dissection & Pressure Catapulting - Jahiri, Xhevahire (UiT Norges arktiske universitet, 2013)
A very diverse group of fungi capable of forming endophytic associations may have profound consequences for natural ecosystems as well as for cultivated plants. Fungal endophytes may benefit their host plants by producing secondary metabolites, and may be an important source for bioactive antimicrobial compounds, used in agriculture, commercial industry, and in medicine. Earlier studies on endophytes using traditional isolation methods were subject to many technical limitations. Molecular approaches available today can overcome some of these technical limitations and provide a more accurate picture of endophytic associations in natural habitats. In this study, 48 grass individuals were examined for the presence of fungal endophytes. Microscope was used to visualize hyphae morphology and estimate the hyphal load, whereas Laser Micro dissection and Pressure Catapulting (LMPC) technique was used as the first stage for their species determination. With LMPC, hyphae are catapulted and collected directly from the host tissues into the caps of microfuge tubes after which they are identified using molecular techniques.The grasses belong to the species of Calamagrostis phragmitoides, Anthoxanthum nipponicum, and Festuca sp. and were collected in meadows along river valleys in eastern Finnmark, northern Norway, during July and August 2008. All grass individuals were found to have several morphologies of hyphae present. From a total of 384 hyphal samples that were catapulted from the three grass species, 36 DNA sequences were successfully isolated by molecular techniques.The success of retrieving hyphal DNA sequences was similar in all three grass species. The DNA sequences retrieved were shown to belong to six classes of fungal endophytes, namely Eurotiomycetes, Dothideomycetes, Sordariomycetes, Leotiomycetes and Pezizomycetes, and Exobasidiomycetes. Hyphal load or hyphal morphology was not found to be important for the success of catapulting and PCR amplification. In addition, hyphal morphology was not predictive of ...